Penyuluhan tentang pentingnya bijak dalam berbahasa di media sosial bebrbasis neurosains bagi guru dan siswa - Eli Syarifah Aeni; Reka Yuda Mahardika; Suhud Aryana; Yusep Ahmadi F (IKIP SILIWANGI, 2022)
This dedication is motivated by the many legal problems that are motivated by the unwise language on social media. One of them, social media at this time is often misused by humans to spread false news and spread hatred. Not infrequently people who do not have the awareness and knowledge about the use of social media are carried away by the current. As a result, the community will potentially get into legal problems. Currently, the use of social media that contains such violations will be subject to the ITE Law. The purpose of this service is to provide counseling as a solution for people who are considered to still do not have the awareness and language skills on social media wisely, well, and politely. This service method is by providing planned and structured counseling to teachers and students of the Miftahul Ihsan Al Banjary Foundation, Banjar City. The results of observations and questionnaires showed that the teacher and student participants were enthusiastic and gained knowledge about polite language on social media. It is hoped that this activity will provide knowledge and increase the awareness of teachers and students of the Miftahul Ihsan Al Banjary Foundation in Banjar City in wise and polite language on social media.